2016
DOI: 10.1002/gj.2769
|View full text |Cite
|
Sign up to set email alerts
|

Genesis and tectonic implications of cumulate pyroxenites and tectonite peridotites from the Nagaland–Manipur ophiolites, Northeast India: constraints from mineralogical and geochemical characteristics

Abstract: The Nagaland–Manipur ophiolites (NMO) of Northeast India forms a part of the Tethyan ophiolites and comprises a suite of tectonite peridotites and cumulate mafic–ultramafic sequence with mafic extrusive–intrusive rocks, felsic intrusives and oceanic pelagic sediments along with minor podiform chromitites. However, sheeted dykes, which are considered as a significant component of ophiolites, are absent in the NMO. The tectonite peridotites are distinguished from the cumulate pyroxenites by the presence of pyrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 98 publications
(154 reference statements)
0
23
0
Order By: Relevance
“…Some claimed that these two ophiolite belts are genetically unrelated; the eastern belt is a continuation of the Bangong‐Nujiang Suture (BNS) of the Meso‐Tethys Ocean, whereas the western belt is a continuation of the IYTS and represents relics of the Neo‐Tethys Ocean (Liu et al, 2016). The NMO in the western belt has recently gained attention due to the availability of geochemically diverse mafic and ultramafic rocks (Ao, Bhowmik, & Upadhyay, 2020; Bhowmik & Ao, 2016; Ghosh et al, 2017; Khogenkumar et al, 2016; Kingson, Bhutani, Dash, Sebastian, & Balakrishnan, 2017; Ovung et al, 2017; Singh, 2013; Singh et al, 2013; Singh et al, 2017). Geochemical studies on mantle peridotites from the NMO suggested that they are restites that went through low degree partial melting (~15%) of adiabatic process in a spreading centre (Devi & Singh, 2011; Ningthoujam, Dubey, Guillot, Fagio, & Shukla, 2012; Singh, 2009, 2013; Singh, Singh, Devi, & Singh, 2008; Soibam, Khuman, & Subhamenon, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some claimed that these two ophiolite belts are genetically unrelated; the eastern belt is a continuation of the Bangong‐Nujiang Suture (BNS) of the Meso‐Tethys Ocean, whereas the western belt is a continuation of the IYTS and represents relics of the Neo‐Tethys Ocean (Liu et al, 2016). The NMO in the western belt has recently gained attention due to the availability of geochemically diverse mafic and ultramafic rocks (Ao, Bhowmik, & Upadhyay, 2020; Bhowmik & Ao, 2016; Ghosh et al, 2017; Khogenkumar et al, 2016; Kingson, Bhutani, Dash, Sebastian, & Balakrishnan, 2017; Ovung et al, 2017; Singh, 2013; Singh et al, 2013; Singh et al, 2017). Geochemical studies on mantle peridotites from the NMO suggested that they are restites that went through low degree partial melting (~15%) of adiabatic process in a spreading centre (Devi & Singh, 2011; Ningthoujam, Dubey, Guillot, Fagio, & Shukla, 2012; Singh, 2009, 2013; Singh, Singh, Devi, & Singh, 2008; Soibam, Khuman, & Subhamenon, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the slowly cooling, unzoned minerals are indicative of crystallisation in a high-pressure environment [96]. The existence of highly magnesian olivine, pyroxene neoblasts and the absence of plagioclase are in line with high pressure crystallisation of basaltic melts [97]. Al contents of the clinopyroxenes and orthopyroxenes in both lithologies are compatible with formation in a SSZ regime.…”
Section: Tectonic Settingmentioning
confidence: 87%
“…But currently with the availability of sophisticated instrumental analytical techniques, such as INAA, ICP-AES, ICP-MS, and HR-ICP-MS, these tasks have become relatively easy. Among them ICP-MS and HR-ICP-MS are most commonly used for REE determination in different kinds of rocks because of their speed, multi-element capability, high sensitivity wide linear dynamic range, fewer interferences, ease of operation and accuracy, and undoubtedly ICP-MS (including HR-ICP-MS) is the best choice (Balaram, 2019;Singh et al, 2016).…”
Section: Rare Earth Elementsmentioning
confidence: 99%